PRELIMINARY RESULTS OF THE APPLICATION OF COMPUTERIZED BREATHING CONTROL AS AN AUXILIARY METHOD OF PSYCHOLOGICAL REHABILITATION - Sharypanov, A. V.; Vyshnevskyi, V. V.; Chaikovsky, I. A.; Syvak, O. V.; Pukavska, L. A. (Medical Informatics and Engineering, 2023)
Background. The urgency of conducting research of this type is due to the large number of people who need psychological rehabilitation as a result of the COVID-19 pandemic and the war in Ukraine. The goal of the work was to verify the effectiveness of automated breathing control technology application during consultations of psychologists with clients who had a high level of anxiety. Materials and methods. Results. Breathing techniques, including yogic ones, have long been known as having no contraindications for a physically healthy person. The effectiveness of breathing formulas, which are used during breathing exercises, for example for calming and relaxation, has been tested by time. The effectiveness of yogic breathing techniques is related to the ability of yogis to "hear their own pulse", which is achieved by long term trainings. The usefulness of binding such activity to the internal rhythms of a specific person is explained by the scientific directions of "chronobiology" and "chronomedicine". However, most people who could benefit from breathing exercises do not have time to learn to hear their own pulse because they need immediate help. In their work, psychologists teach clients the skills of stabilization and self-regulation, as well as their practical application in everyday life to quickly improve their psycho-emotional state thanks to the physiological characteristics of a person and without involving additional resources. Clients are encouraged to use abdominal breathing by square or 4-7-8 technique. Here, time intervals are measured in absolute units, such as seconds, steps, etc. Conclusions. The widespread use of mobile devices and low-cost wireless heart rate monitors has made it possible to implement automated technology for breathing control in which breathing formulas are personalized by pulse beats detected in real time. Preliminary results of a monitoring study in which computerized breathing control was implemented as an additional auxiliary method during psychological rehabilitation are presented.